2008
DOI: 10.1002/art.23930
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal factors and adult‐onset lupus

Abstract: Objective. Some evidence suggests that perinatal factors, including birth weight and breastfeeding, may influence the occurrence of autoimmune rheumatic diseases. However, few studies have investigated these factors in patients with systemic lupus erythematosus (SLE). Therefore, we evaluated the role of birth weight, being breastfed, and preterm birth on the incidence of SLE in participants in the Nurses' Health Study (NHS) and the Nurses' Health Study II (NHSII). Methods. We studied 87,411 NHS participants an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 29 publications
2
24
0
Order By: Relevance
“…Meanwhile, preterm birth was recently found to be a risk factor for systemic lupus erythematosus and related autoimmune conditions [17]. The immature immune system of a preterm neonate may be ill-suited to long-term alterations to the immune system.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, preterm birth was recently found to be a risk factor for systemic lupus erythematosus and related autoimmune conditions [17]. The immature immune system of a preterm neonate may be ill-suited to long-term alterations to the immune system.…”
Section: Discussionmentioning
confidence: 99%
“…The same group has shown an association between high birth weight and a greater risk of developing adult RA in the NHS. Interestingly, they have also shown that higher birth weight was associated with an increased incidence of developing systemic lupus erythematosus in the same cohort 13 . Other groups have shown associations between high birth weight and development of RA 14 , and low birth weight being protective for the development of See Early life factors and adult-onset RA, page 32…”
Section: Editorial Can the Events Of Early Life Influence The Developmentioning
confidence: 82%
“…Simard et al indicated that participants that experienced a preterm birth had a statistically significant, 1.9-fold higher incidence of SLE (95% CI 1.2–3.0). [47] A population-based nested case–control study showed that there was a 2.4-fold increased odd of SLE among males born preterm (95% CI 1.09–5.36). [48] Our multivariate analysis revealed that patients with preterm birth displayed a significant 2.09-fold increased HR for SLE (95% CI 1.42–3.06) (see Table 3).…”
Section: Discussionmentioning
confidence: 99%